The smallest but fastest: ecophysiological characteristics of traps of aquatic carnivorous Utricularia - Adamec, Lubomír (Plant signaling & behavior, 2011)
Aquatic Utricularia species usually grow in standing, nutrient-poor humic waters. They take up all necessary nutrients either directly from the water by rootless shoots or from animal prey by traps. The traps are hollow bladders, 1-6 mm long with elastic walls and have a mobile trap door. The inner part of the trap is densely lined with quadrifid and bifid glands and these are involved in the secretion of digestive enzymes, resorption of nutrients and pumping out the water. The traps capture small aquatic animals but they also host a community of microorganisms considered as commensals. How do these perfect traps function, kill and digest their prey? How do they provide ATP energy for their demanding physiological functions? What are the nature of the interactions between the traps and the mutualistic microorganisms living inside as commensals? In this mini review, all of these questions are considered from an ecophysiologist's point of view, based on the most recent literature data and unpublished results. A new concept on the role of the commensal community for the plants is presented.
Keywords: Aquatic Organisms; ekosystém; vodní organismy; voda; Ecosystem; Water; Magnoliopsida; Food Chain; potravní řetězec; Oxygen; kyslík